Are large-scale distributional shifts of the blue-winged macaw (Primolius maracana) related to climate change? - Conti Nunes, Maria Flavia; Galetti, Mauro; Marsden, Stuart; Pereira, Ricardo Scachetti; Peterson, A. Townsend (Wiley-Blackwell, 2007)
Aim To evaluate whether observed geographical shifts in the distribution of the blue-winged macaw (Primolius maracana) are related to ongoing processes of global climate change. This species is vulnerable to extinction and has shown striking range retractions in recent decades, withdrawing broadly from southern portions of its historical distribution. Its range reduction has generally been attributed to the effects of habitat loss; however, as this species has also disappeared from large forested areas, consideration of other factors that may act in concert is merited.Location Historical distribution of the blue-winged macaw in Brazil, eastern Paraguay and northern Argentina.Methods We used a correlative approach to test a hypothesis of causation of observed shifts by reduction of habitable areas mediated by climate change. We developed models of the ecological niche requirements of the blue-winged macaw, based on point-occurrence data and climate scenarios for pre-1950 and post-1950 periods, and tested model predictivity for anticipating geographical distributions within time periods. Then we projected each model to the other time period and compared distributions predicted under both climate scenarios to assess shifts of habitable areas across decades and to evaluate an explanation for observed range retractions.Results Differences between predicted distributions of the blue-winged macaw over the twentieth century were, in general, minor and no change in suitability of landscapes was predicted across large areas of the species' original range in different time periods. No tendency towards range retraction in the south was predicted, rather conditions in the southern part of the species' range tended to show improvement for the species.Main conclusions Our test permitted elimination of climate change as a likely explanation for the observed shifts in the distribution of the blue-winged macaw, and points rather to other causal explanations (e.g. changing regional land use, emerging diseases).
Keywords: Blue-winged macaw; climate change; ecological niche modelling; geographic distributions; range retraction; South America